PENGARUH KOMPENSASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN ( Studi pada bagian produksi PT. Kayamas Intitama Semarang) (Students' Journal of Economic and Management, 2013)
This study is a study that examined the effect of compensation, leadership and work environment on the performance of employees in the production of PT. Kayamas Intitama Semarang. This study aims to examine and analyze the effect of compensation, leadership and work environment on the performance of employees in the production of PT. Kayamas Intitama Semarang. In this study, the study used a sample of 90 respondents to the data collection methods used in this research is using questionnaires (questionnaire) by distributing a questionnaire to the respondent in order to obtain information. The data were analyzed using factor analysis to test the validity of the questionnaire items, Cronbach alpha formula to test the reliability of the instrument, regression analysis, to examine the effect of partially magnitude of each independent variable were tested with the coefficient of determination (R2) and the effect of partially prove their each independent variable. The results of the research are: (1) Compensation and significant positive effect on employee performance, the better the compensation will better the performance of employees. (2) Leadership and significant positive effect on employee performance, the better the leadership will better the performance of employees. (3) The working environment and significant positive effect on employee performance, the better the better the conducive and employee performance.Keywords: Compensation, Leadership, work environment and employee performance